Health-related quality of life with emotional and behavioral outcomes in renal transplant recipients: A study from a tertiary center in North India - Anant Giri; Nripesh Sadasukhi; Trilok Chand Sadasukhi; Manish Gupta; Hotilal Gupta; Ashish Sharma; Sonia Goswami; Ankit Modi (Indian Journal of Transplantation, 2023)
Introduction: Kidney transplantation is the treatment of choice for patients suffering from end-stage renal disease and health-related quality of life (HRQoL) is routinely used for measuring the outcome. Although the generic HRQoL questionnaire provides useful information on multiple dimensions, they fail to capture emotional and behavioral components of well-being, which is supplemented by the Transplant Effects Questionnaire (TxEQ). The present research studies the impact of these two questionnaires on various parameters affecting the health of kidney transplant recipients. Methodology: This cross-sectional study included 500 postrenal transplant patients within 5 years of transplant (18–70 years) evaluating HRQoL using a Short Form Survey-36 Questionnaire and emotional/behavioral outcomes using a TxEQ. Results: Mean age of participants was 44.92 ± 5.86 years and males constituted the majority (>75%). The mean physical component score (PCS) was 41.3 ± 9.2 and the mental component score (MCS) was 48.1 ± 8.4. The highest score was observed for bodily pain, followed by role limitations attributable to emotional problems (RE). The PCS was significantly higher among younger participants, among males, among participants who have got a transplant >24 months ago, and among participants who had serum creatinine levels <2 mg/dl (*P < 0.05). However, the mental component score did not differ significantly in any of the matched variables. In TxEQ, medication adherence had the highest mean score, followed by perceived responsibility toward others. Conclusion: In our study, we concluded that reduced physical functioning among female gender, illiterate patients, with increasing age, in employed section, and with associated comorbidities such as hypertension and with a history of rehospitalization.